Nlrp3 Prevents Early Renal Interstitial Edema and Vascular Permeability in Unilateral Ureteral Obstruction - Pulskens, Wilco P.; Butter, Loes M.; Teske, Gwendoline J.; Claessen, Nike; Dessing, Mark C.; Flavell, Richard A.; Sutterwala, Fayyaz S.; Florquin, Sandrine; Leemans, Jaklien C. (PloS one, 2014)
Progressive renal disease is characterized by tubulo-interstitial injury with ongoing inflammation and fibrosis. The Nlrp3 inflammasome contributes to these pathophysiological processes through its canonical effects in cytokine maturation. Nlrp3 may additionally exert inflammasome-independent effects following tissue injury. Hence, in this study we investigated potential non-canonical effects of Nlrp3 following progressive renal injury by subjecting WT and Nlrp3-deficient (-/-) mice to unilateral ureter obstruction (UUO). Our results revealed a progressive increase of renal Nlrp3 mRNA in WT mice following UUO. The absence of Nlrp3 resulted in enhanced tubular injury and dilatation and an elevated expression of injury biomarker NGAL after UUO. Moreover, interstitial edema was significantly elevated in Nlrp3-/- mice. This could be explained by increased intratubular pressure and an enhanced tubular and vascular permeability. In accordance, renal vascular leakage was elevated in Nlrp3-/- mice that associated with reduced mRNA expression of intercellular junction components. The decreased epithelial barrier function in Nlrp3-/- mice was not associated with increased apoptosis and/or proliferation of renal epithelial cells. Nlrp3 deficiency did not affect renal fibrosis or inflammation. Together, our data reveal a novel non-canonical effect of Nlrp3 in preserving renal integrity and protection against early tubular injury and interstitial edema following progressive renal injury.